PEMBUATAN BIOBRIKET DARI CAMPURAN KULIT KACANG TANAH DAN TEMPURUNG KEMIRI DENGAN MENGGUNAKAN METODE KARBONISASI - Kusyanto Kusyanto; Rinda Handayani; Andri Kurniawan (Politeknik Negeri Samarinda, 2022)
Biobriquettes are one of the alternative energy solid fuels that are the basic materials of a biomass mixture. The addition of the word bio to briquettes is due to the addition of biomass as a raw material. Peanut skin and hazelnut shell that is only wasted resulted in the accumulation of agricultural waste in the form of peanut skin and hazelnut shell. To overcome this, further research is needed to have added value. In this study, it aims to influence the effect of the comparison of the composition of raw materials of peanut skin charcoal and hazelnut shells against proximate values and heat values. This study used carbonization methods. From the results of the analysis obtained the highest heat value in the treatment E was 6006 Cal/gr. Briquette water content ranges from 4 - 5% and the lowest water content was obtained in treatment B which was 4.08%. The results of the analysis of ash levels ranged from 11 - 17% and obtained the lowest ash levels in treatment B, which was 11.92%. Volatile matter results ranged from 26 - 28% and the lowest Volatile Matter level at D treatment was 26.57% and fixed carbon results ranged from 50 - 55% and the highest fixed carbon result was at 55.96%.Keywords: bean skin, hazelnut shell, biobriquette, proximate